2014
DOI: 10.1890/14-0310.1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting elevational diversity patterns between eukaryotic soil microbes and plants

Abstract: The diversity of eukaryotic macroorganisms such as animals and plants usually declines with increasing elevation and latitude. By contrast, the community structure of prokaryotes such as soil bacteria does not generally correlate with elevation or latitude, suggesting that differences in fundamental cell biology and/or body size strongly influence diversity patterns. To distinguish the influences of these two factors, soil eukaryotic microorganism community structure was investigated in six representative vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
143
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(164 citation statements)
references
References 71 publications
18
143
3
Order By: Relevance
“…Our finding here L linear regression, Q quadratic regression **P < 0.01, *P < 0.05 parallels the studies of microbes that bacterial diversity do not follow the elevational diversity patterns of macroorganisms (Fierer et al 2011;Shen et al 2014). Hillebrand and Azovsky (2001) pointed out that small size strongly promotes high dispersal ability, and large population size and short generation times may result in a better chance of long-distance dispersal (Finlay 2002;McCain 2006).…”
Section: Diversity Of Soil Bacterial Communitysupporting
confidence: 84%
See 1 more Smart Citation
“…Our finding here L linear regression, Q quadratic regression **P < 0.01, *P < 0.05 parallels the studies of microbes that bacterial diversity do not follow the elevational diversity patterns of macroorganisms (Fierer et al 2011;Shen et al 2014). Hillebrand and Azovsky (2001) pointed out that small size strongly promotes high dispersal ability, and large population size and short generation times may result in a better chance of long-distance dispersal (Finlay 2002;McCain 2006).…”
Section: Diversity Of Soil Bacterial Communitysupporting
confidence: 84%
“…As the most important feature in determining bacterial distribution in our study, soil pH generally found to be the most important identifiable factor controlling soil bacterial diversity. The important role of pH has recently been found to influence bacterial diversity on horizontal soils (Griffiths et al 2011;Philippot et al 2013), and vertical soils across an elevational gradient (Xiong et al 2012;Shen et al 2014). The finding that diversity of bacteria was positively related to pH was consistent with that from a pH controlled experiment indicated lower pH was stressful for most taxa (Rousk et al 2010).…”
Section: Diversity Of Soil Bacterial Communitysupporting
confidence: 63%
“…Nonmetric multidimensional scaling (NMDS) ordinations were generated using the vegan tool of R, version 2.3.0 (49), on the basis of Bray-Curtis dissimilarities. In order to describe biodiversity, which incorporates the phylogenetic difference between species, Faith's index (50), which has been extensively used in the literature (14,26), was used to calculate phylogenetic diversity. Species-level measurement was assessed by use of the Shannon index (H=).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the pyrosequencing profiles of rRNA genes indicated that both bacterial and fungal communities clearly differed in three plateau habitats. In a montane elevation gradient study, vegetation-type zonations were associated with distinct microeukaryotic, fungal, and protistan microbial communities (26). Microscopic analysis showed that the bacterial and microeukaryotic structure changed with plant species in Sphagnum peatlands when perturbed by warming (35).…”
mentioning
confidence: 96%
See 1 more Smart Citation